Effects of Ophiopogon japonicus oligosaccharides on type 2 diabetes in rats via modulation of gut microbiota and metabolites - Yang, Tingyu; Chen, Baoting; Fang, Jia; Li, Zilin; Liu, Yiming; Lin, Aihua (Frontiers in Pharmacology, 2025)
IntroductionOphiopogon japonicus oligosaccharides (OJO) is a bioactive component extracted and purified from the traditional Chinese medicinal herb Radix Ophiopogonis (Maidong) with significant hypoglycemic effects, although its mechanism of action remains to be further studied.MethodsThis study used a high-fat diet supplemented with streptozotocin to establish a rat model of type 2 diabetes mellitus (T2DM). OJO was administered at low, medium, and high doses for four consecutive weeks. Biochemical indices of glucose and lipid metabolism were measured, and feces, serum, and colonic contents were collected for 16 S rRNA gene sequencing, metabolomics, and gas chromatography–mass spectrometry.ResultsOJO treatment significantly alleviated polyuria and weight loss, ameliorated insulin resistance, and improved glucose and lipid metabolism disorders in T2DM rats. OJO also modulated gut microbiota composition by increasing the Firmicutes-to-Bacteroidota ratio and regulating key bacterial genera, including decreased Lactobacillus and Prevotella and increased unclassified_f_Lachnospiraceae, Faecalibaculum, norank_f_norank_o_Clostridia_UCG-014, Christensenellaceae_R-7_group, Romboutsia, and UCG-005. Additionally, OJO significantly reduced acetic acid and propanoic acid levels. Serum untargeted metabolomic analysis revealed that OJO modulated 40 diabetes-associated metabolites, primarily linked to the synthesis and metabolic pathways of aromatic amino acids and bile acids. Correlation analysis identified significant connections between these metabolic alterations and specific gut microbiota.ConclusionOJO exhibits therapeutic potential for T2DM, possibly by regulating gut microbiota and associated metabolites.